Mouse genetics and transgenics : a practical approach - Jackson, Ian J.; Abbott, Catherine M. (Practical approach series, 2000)
"Mouse Genetics and Transgenics: A Practical Approach is set to become a classic laboratory guide to the mouse. All major aspects are covered including: care and husbandry; archiving stocks as frozen embryos or sperm; mapping mutations and phenotypic trait loci; genetic and physical mapping of genomes; mouse cytogenetics and FISH; making new mutations by chemical mutagenesis or by directed mutagenesis through targeting in ES cells; making transgenic mice from plasmids, BACs and YACs; spatial analysis of gene expression. Details of the many databases for mouse researchers are also included together with specific guidance on information gathering and dissemination via the Internet." "This book will be an invaluable laboratory companion for every mouse researcher and for human geneticists who want to turn to the mouse model to address problems of human disease."--Jacket